(untitled) (Agricultural Engineering, 2023)
In precision agriculture, it is possible to use satellite monitoring of fields. Satellite monitoring systems allow you to get free images with a resolution of up to 10 m per pixel, which is sufficient to determine the state of vegetation of plants on such indicators as the normalized vegetation index NDVI. However, the NDVI indicator already indicates the existing problems of correction which will not help to restore the lost yield of crops, but only helps to prevent further losses. Using the NDSI soil salinity index, it is possible to determine the difference in its properties from spectral images. Also, you can study the vegetation of plants in the early stages of their development, in fact immediately after germination. Soil-adjusted vegetation index, such as MSAVI, is used for this purpose. Studies indicate the possibility of using NDSI and MSAVI indicators for early diagnosis of confirmed crops NDVI and NDRE (indicating chlorophyll activity in plants) at later stages of their development. Studies conducted on soybean, spring barley and maize crops sown in the spring of 2021 indicate a correspondence between raster field maps show-ing the above indices made from March to July. Statistical analysis of raster images of field maps using specialized software showed a correlation between NDSI and MSAVI in March and May, respectively, with NDVI and NDRE indexes in June and July. Therefore, it is possible to judge the expediency of using NDSI and MSAVI indicators for early diagnosis of possible problems with plant vegetation, as well as for the creation of maps of differential fertilization.